Can water, energy, and food policies in support of solar irrigation enable gender transformative changes? Evidence from policy analysis in Bangladesh and Nepal - Khadka, Manohara; Uprety, Labisha; Shrestha, Gitta; Shakya, Shristi; Mitra, Archisman; Mukherji, Aditi (Frontiers in Sustainable Food Systems, 2024)
Solar irrigation pump (SIP) is emerging as a popular technology to address water, energy and climate change challenges in South Asia, while enhancing livelihoods and food security. SIPs are deemed to be a women-friendly renewable energy technology (RET) due to its design, operation system and safety. While the gender dimensions of natural resources are well documented, the extent to which the water, energy and food (WEF) policies-including policies to promote SIP technologies in the countries of South Asia-conceptualize and operationalize gender equality and social inclusion (GESI) is not well understood. Therefore, we reviewed 39 WEF sectoral policies of Bangladesh and Nepal by deploying a gender-transformative analysis approach to rank the policies on a continuum ranging from scale of 0-3 (denoting gender-blindunaware, gender-aware, gender-responsive and gender-transformative). We find that the Governments in both the countries commit to gender equality and women's advancement in the WEF sector policies, institutions and decision-making by ensuring gender and justice principles in the Constitutions and national development frameworks. However, these higher-level aspirational principles are not always translated to the WEF sector policies. We find that the WEF policies are aware of the need to include GESI and social equity in sectoral programming, yet operational rules for their implementation often fail to challenge structural barriers. Such barriers hinder women and marginalized groups from participating in and benefiting from WEF policies, including the deployment of SIP technologies. This calls for a transformation, not only in the project implementation, but also of the policymaking processes of WEF sectors in the South Asia region.